Aortic valvuloplasty under echocardiographic guidance in a minor infant at a national referral center in Peru: case report - Catalán Cabrera, Alex (2024)
Aortic stenosis is a congenital heart defect that causes a fixed left ventricular outflow obstruction with a progressive course. Symptomatology in neonates and young infants resembles congestive heart failure. In addition, the diagnosis of this condition is made by imaging, through echocardiography. On the other hand, treatment can be surgical or interventional under fluoroscopic guidance, depending on the hospital in which it is performed. We describe the case of a minor infant patient who presented severe aortic valve stenosis; however, the fluoroscopy equipment was not available at the time of the emergency to perform the appropriate procedure, therefore, an aortic valvuloplasty was performed under echocardiographic guidance without complications.